STRUCTURE AND PHOTOELECTROCHEMICAL PROPERTIES OF ELECTRODEPOSITED Cu2ZnSn(S,Se)4 FILMS - Urazov Kazhmukhan Amankeldievich,; Dergacheva Margarita Borisovna,; Gremenok Valery Feliksovich ,; Zaretskaya Ellen Petrovna, (Academic Scientific Journal of Chemistry, 2019)
A one-step electrochemical synthesis of Cu2ZnSnSe4 (CZTSe) and Cu2ZnSnS4 (CZTS) films on Mocoated glass from aqueous electrolytes containing both Cu+2, Zn+2, Sn+2 and Se+4 or S+4 ions has been developed. Electrodeposition was performed at a constant potential with subsequent annealing at a temperature of 450 °C in air for 60 minutes. Cu2ZnSn(S0.96,Se0.04)4 films were obtained by sulfurizing electrodeposited Cu2ZnSnSe4 layers in a sulfur atmosphere at 500 °C for 60 minutes. The structure and phase composition of the films was confirmed by XRD and Raman spectroscopy. It was confirmed by the PEC method that all films had p-conductivity. It was established that a change in the chemical composition of the films affects the electrophysical properties, and for Cu2ZnSn(S,Se)4 layers the photoresponse was 5-6 times higher than for four component compounds